Air Temperature: Relationship with Soil Temperature and Evaporation and Congeniality to Crops in Koraput District of Orissa - Sudhishri, Sus; Dass, A.; Patnaik, U.S. (Journal of Soil and Water Conservation, 2022)
Temperature is an important climatic parameters, which controls the environment and affects the soil temperature and evaporation. An attempt was made to work out the relationship between them so that commonly available temperature data could be used for determining soil temperature and evaporation and finding its congeniality to crops and also its diurnal and annual range. Soil temperature at 5, 10 and 20 cm depths were significantly positively correlated with maximum and minimum ambient temperature. It was found that during morning hours the change in soil temperature at 5 and 10 cm depths was more with change in minimum air temperature, whereas at 20 cm depth, the effect of change in maximum air temperature was more, during evening hours soil temperature was higher at 5 cm depth and was affected more by change in maximum temperature. A strong correlation was also observed between average weekly and monthly evaporation with respective air temperature. The difference between the annual mean maximum and minimum temperature for the area is 12.42°C and the Growing Diegree Days (GDD) for upland, medium land and jhola land rice are 1998.4, 2233.6 and 3452.1 units respectively and for ragi is 1926.1 units. It was also found that temperature was favrouable for crops like rice, millets, groundnut and peas.